Optimizing Law Enforcement Against Enforcement Of Online Gambling Promotion Cases by Influencer (Case Study of Gunawan Also Known As Sadbor) - Ramadhan, Raflisyah; Aji Lukman Ibrahim (KRTHA BHAYANGKARA, 2025)
This research investigates the application of the principle of equality before the law in Indonesia, focusing on the case of influencer Gunawan Also Known As Sadbor, who was involved in promotion of online gambling. The rise of online gambling, exacerbated by influencer promotion, poses significant social and legal challenges. This study utilizes a normative juridical methodology, examining primary and secondary legal resources, including laws, court decisions, and scholary articles, to assess the consistency and fairness of law enforcement in online gambling promotion cases. The research highlights inconsistencies in the handling of Sadbor’s case compared to other similiar cases, particularly regarding his detention and subsequent appointment as an anti-online gambling ambassador. This discrepancy indicates a potential failure to uphold the principle of equality before the law. The research findings emphasize the need for law enforcement to ensure impartial application of the law, increase public trust, and effectively prevent the promotion of online gambling. This study enhances understanding of the challenges in enforcing laws related to online gambling and the improtance of adhering to the principle of equality before the law for a fair and equal legal system.